1981
DOI: 10.1103/physrevlett.46.1322
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Structure Transition in Ne(P03) on Ne(

Abstract: The co His ion-induced exothermic fine-structure transition Ne( 3 P 0 )-Ne( 3 P 2 ) has been observed in a crossed-effusive-beam experiment, by measuring the time of flight of metastable atoms scattered perpendicularly to the incident-beam plane. In this direction, the elastic scattering is kinematically discriminated. The identification of the transition is achieved by pumping 3 P 0 or 3 P 2 levels with a cw dye laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…3.2 INELASTIC SCATTERING. 2013 In fact, several experimental data indicate that this good agreement between experiment and calculations based on purely elastic scattering is no longer preserved when the collision energy becomes larger than about 90 meV : (i) the elastic cross sections measured by Beyer et al [10] at 111 meV and 143 meV exhibit some anomalies in their u-g interference pattern; (ii) by detecting metastable atoms scattered in the direction perpendicular to the incident beam planewhich eliminates any elastic or endothermic collision process - [12], we have observed the superelastic fine structure transition :…”
Section: Purely Elastic Collision -The Argumentmentioning
confidence: 98%
“…3.2 INELASTIC SCATTERING. 2013 In fact, several experimental data indicate that this good agreement between experiment and calculations based on purely elastic scattering is no longer preserved when the collision energy becomes larger than about 90 meV : (i) the elastic cross sections measured by Beyer et al [10] at 111 meV and 143 meV exhibit some anomalies in their u-g interference pattern; (ii) by detecting metastable atoms scattered in the direction perpendicular to the incident beam planewhich eliminates any elastic or endothermic collision process - [12], we have observed the superelastic fine structure transition :…”
Section: Purely Elastic Collision -The Argumentmentioning
confidence: 98%
“…Electrostatic deflecting plates eliminate charged particles from the atomic beam. Previous experiments [5] have shown that 3P2 and 3po metastable levels are populated proportionally to their statistical weights (5 : 1).…”
Section: Introductionmentioning
confidence: 94%
“…The angular dependence of the scattered intensity and the velocity dependence of the differential cross-section in the backward scattering direction are given. Differential cross-sections in metastable Ne on Ne collisions at thermal energies have recently been measured in supersonic [ 1,2] or effusive [3,4] crossed beam experiments. These measurements are a stringent test of the validity of the calculated Ne!…”
mentioning
confidence: 99%
“…As it has already been shown in the case of the Ne! system [4,5], a more complete knowledge of the involved molecular states, as well as their mutual couplings, needs a detailed study of eventual inelastic processes (essentially the fine-structure transitions). This work is now in progress.…”
mentioning
confidence: 99%